HEMODYNAMIC CHANGES IN CHILDREN WITH INFECTIOUS DISEASES COMPLICATED BY ABDOMINAL COMPRESSION SYNDROME - Yevtushenko, V.V.; Markov, A.I.; Kramarev, S.O. (World of Medicine and Biology, 2019)
We aimed to study changes of blood circulation and markers of gastrointestinal damage in children with intraabdominal hypertension and abdominal compartment syndrome. We have studied 6 cases of abdominal compartment syndrome in children with infectious diseases. It was found that increased abdominal pressure and abdominal compartment syndrome were associated with significant elevation of intestinal serum biomarker I-FABP (13.44±4.58 ng/ml amid elevated abdominal pressure vs 2.65±1.25 amid normal abdominal pressure), higher cardiac output (6.0±0.57 l/min/m2 vs 4.3±0.34 l/min/m2), decreased diastolic blood flow velocity in renal (3.4±1.08 cm/s vs 18.7±1.58 cm/s) and superior mesenteric (5.1±0.87 cm/s vs 17.5±3.90 cm/s) arteries, and elevated peripheral resistance index (RI) in the renal artery (0.92±0.02 vs 0.70±0.02, p
Keywords: abdominal compartment syndrome; hemodynamic. FABP. children